Concretization as a Mechanism of Change in Psychodrama: Procedures and Benefits - Kushnir, Aviv; Orkibi, Hod (Frontiers in Psychology, 2021)
Concretization is a concept that has different meanings in different psychological theories and varying manifestations in different psychotherapies. In psychodrama, much of the available information on concretization draws on Moreno's initial conceptualization, descriptive case studies, and interpretations in the various approaches. However, concretization has not been empirically studied as a concept or as a therapeutic mechanism of change. Therefore, the purpose of this qualitative study was to generate an empirically-based conceptualization and operationalization of concretization as well as to identify its clinical benefits in psychodrama. To this end, semi-structured in-depth interviews were conducted with seven experienced psychodrama therapists. Using a grounded theory approach for the data analysis, the model that emerged consists of three pathways towards concretization: realistic concretization, symbolic concretization, and integrated concretization. The findings suggest a sequential multi-step operation that can be linear or nonlinear, depending on the protagonist's need. The findings also underscore four benefits of concretization as a mechanism of change in psychodrama: reducing the ambiguity of the problem, externalizing the protagonist's problem, enhancing the therapist-protagonist therapeutic bond, and bypassing the protagonist's defense mechanisms. The model is discussed in light of the findings and the literature and future directions are suggested.